The Free Hajj: Virtual Reality in Manasik Hajj Training Education - Dadan Sumardani; Rahma Rosaliana Saraswati; Ulfatun Widiastuti; Komala Komala; Winda Dewi Listyasari (Al-Hayat Al-Istiqomah Foundation, 2020)
Hajj is one of the five pillars of Islam and is obligatory for qualified Muslims. This study aims to make a virtual reality application for hajj simulation. This study uses descriptive analysis method.The result of this research is an application that consists of 6 features, namely: features (hajj series, hajj series guide, Arabic language, floor plans, frequently asked questions, instructions for use).The Free Hajj will learn how to perform the Hajj not just a theory but also presents ideas, practices and actual conditions. Like being directly in Mecca.